Speciation and biogeochemical behavior of perfluoroalkyl acids in soils and their environmental implications: A review - Chao Guo; Shiwen Hu; Pengfei Cheng; Kuan Cheng; Yang Yang; Guojun Chen; Qi Wang; Ying Wang; Tongxu Liu (Eco-Environment & Health)
Perfluoroalkyl acids (PFAAs) are emerging organic pollutants that have attracted significant attention in the fields of environmental chemistry and toxicology. Although PFAAs are pervasive in soils and sediments, there is a paucity of research regarding their environmental forms and driving mechanisms. This review provides an overview of the classification and biotoxicity of per- and polyfluoroalkyl substances (PFAS), organic pollutant forms, PFAS extraction and analytical methods, the prediction of PFAS distribution in soils, and current PFAS remediation strategies. Four predominant PFAA forms have been proposed in soils: (i) aqueous-extracted PFAAs, (ii) organic-solvent extracted PFAAs, (iii) embedded or sequestered PFAAs, and (iv) covalently bound PFAAs. Furthermore, it suggests suitable extraction methods and predictive models for different PFAA forms, which are instrumental in the research on PFAA speciation and prediction in soils. Simultaneously, it was proposed that elemental cycling and microbial activity may affect the speciation of PFAS. Additionally, the categorization of PFAA forms facilitated the analysis of pollution remediation. Understanding the interplay between PFAA speciation, element cycling, and bacterial activity during soil remediation is essential for understanding remediation mechanisms and assessing the long-term stability of remediation methods. Future studies should expand the investigation of varying PFAA forms in different media, consider the potential binding forms of PFAAs to minerals, organic matter, and microbes, and evaluate the possible mechanisms of PFAA speciation variation.